Development of a Team-Project-Based Flip Classroom Learning Model to Enhance Creativity in Teacher Training High School Students - Sri Sumarni; Riska Nurhayati; Ida Nugroho Saputro (Qalamuna)
This study aims to analyze the needs of students' creativity skills in learning, develop a Team Project-Based Flip Classroom Learning Model, and determine the learning model's effectiveness. The research was conducted at one of the vocational schools in Sukoharjo Regency. This research was conducted as research and development using mixed methods in data collection. The instrument's validity for measuring the learning model was evaluated using the Aiken V coefficient, and the model's effectiveness was determined using the N-gain score. The results showed that the team project-based flip classroom learning model is reliable and efficient. This model has three main steps: independent learning, face-to-face learning, and guided learning for self-reflection. These findings imply that teachers, particularly at the vocational education level, can utilize the team-project-based flipped classroom learning model as an alternative learning strategy that emphasizes material mastery and optimizes student creativity development. This model is also relevant for applications in subjects requiring technical skills and creative problem-solving.